The impact of services liberalization on education: Evidence from India - Enrico Nano; Gaurav Nayyar; Stela Rubínová; Victor Stolzenburg (World Trade Organization (WTO), 2021)
This paper studies the impact of services liberalization on education and the gender education gap at the district level in India. We focus on the time period 1987 to 1999 and three services sectors - banking, insurance and telecommunications - which were all state monopolies, have been heavily liberalized in the time frame studied, have relatively high shares of female employment and require high education investments. Our hypothesis is that the national-level liberalization spurred higher investment in education, particularly girls' education, in districts with higher employment growth in these key services sectors. We employ a first difference strategy to control for unobserved time-invariant heterogeneity, use an IV procedure to eliminate other potential sources of bias and control for the simultaneous tariff liberalization. Our results indicate that employment growth in liberalized services sectors is a consistently significant determinant of both the average number of years of schooling (positively) and the gender education gap (negatively). These effects are at least as relevant as those of merchandise trade liberalization, are persistent and driven mostly by the banking and, to a lower extent, the telecommunications sectors. Looking at the transmission channels, we employ a 3SLS strategy and observe that both growing incomes and higher returns to education drive this relationship.
Keywords: F63; I24; J16; L80; O12; 330; Services; liberalization; education; gender; inequality; India